Meningkatkan Kemampuan Siswa Kelas V SDK St. Herman Yosef Paupire dalam Menentukan Tema Cerita dengan Model Pembelajaran DRTA - Petronela Waha Piran (Jurnal Lazuardi, 2022)
This research based on problem that teacher’s has found in class V SDK St. Herman Yoseph Paupire. The problem is that student can’t determine the theme from text. But actually the determine the theme has been learn in class IV, but student in class V can’t determine the theme. This classroom action research used DRTA learning model, to answer the problem. DRTA is a learning model that can increase reading skills and can increase thinking activity. This action research process used two cycles. First cycles show that 2 students very able to determine the theme, 11 students able to determine the theme, and 10 students lack in determine the theme. In second cycles, show that 17 students very able to determine the theme and 5 students able to determine the theme. So, with DRTA learning model can increase the ability of student to determine the theme.